2015
DOI: 10.1016/j.jcf.2015.02.003
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of hemoptysis in cystic fibrosis clinical trials: A retrospective cohort study

Abstract: Background Cystic fibrosis (CF) is characterized by airways infection and inflammation resulting in respiratory complications including hemoptysis. The objectives of this study were to characterize risk of hemoptysis attributable to the underlying disease and in the presence of standard of care therapy. Methods This retrospective cohort study estimated hemoptysis rates overall and by relevant risk factors utilizing adverse event data from longitudinal prospective CF clinical trials. Results Of the 1008 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
1
10
0
1
Order By: Relevance
“…Hemoptysis is often thought to be a manifestation of a PEx (21). Although we specifically excluded patients with massive hemoptysis, the prevalence of milder hemoptysis in our study was comparable to a recent report (22). …”
Section: Discussionsupporting
confidence: 86%
“…Hemoptysis is often thought to be a manifestation of a PEx (21). Although we specifically excluded patients with massive hemoptysis, the prevalence of milder hemoptysis in our study was comparable to a recent report (22). …”
Section: Discussionsupporting
confidence: 86%
“…4,5,17 Using placebo groups from prior randomized control trials, a rate of 8% of patients reported hemoptysis during an average period of 8 months. 18 Risk factors for the development of hemoptysis overlap with pneumothorax and includes worse lung function, older age, as well as the presence of Pseudomonas in sputum cultures.…”
Section: Spirometry 9mentioning
confidence: 99%
“…THOMPSON et al [3] reported that haemoptysis is more common in CF individuals with advanced lung disease (FEV 1 <70% predicted). Although we did not detect an association between FEV 1 and MH in our cohort, consistent with a report by BARBEN et al [4], our study was limited by its retrospective design, the small number of patients, the high proportion of excluded patients, and the difficulty in precisely quantifying haemoptysis-associated blood loss.…”
mentioning
confidence: 99%
“…In a study of 129 French CF patients who died between 2007 and 2010 without receiving lung transplantation, 8.5% of deaths were due to haemoptysis [ 2 ]. Factors associated with an increased risk of haemoptysis in CF patients include older age, advanced lung disease (forced expiratory volume in 1 s (FEV 1 ) <70% predicted), airway colonisation by Pseudomonas aeruginosa [ 3 ], CF-related diabetes, portal hypertension, and liver cirrhosis [ 4 ]. To our knowledge, there have been no studies of the risk factors for the development of massive haemoptysis (MH) in CF patients who have previously experienced an episode of mild-to-moderate haemoptysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation